Psychiatric comorbidity in individuals at‐risk for psychosis: Relationships with symptoms, cognition and psychosocial functioning. Issue 3 (22nd May 2020) - Chang, Wing C.; Ng, Chung Mun; Chan, Kwun Nam; Lee, Hoi Ching; Chan, Suet In; Chiu, Shirley Sanyin; Lee, Ho Ming; Chan, Kit Wa; Wong, Ming Cheuk; Chan, Kwok Ling; Yeung, Wai Song; Chan, Charles Wai Hong; et al.
Abstract: Aim: Psychiatric comorbidity frequently occurs with at‐risk mental state (ARMS) for psychosis. Its relationships with psychopathology, cognition and functioning, however, remain to be further clarified. We aimed to examine prevalence and correlates of psychiatric comorbidity, and its associations with psychosocial functioning and subjective quality‐of‐life (QoL) in a representative sample of Chinese ARMS individuals. Methods: One hundred ten help‐seeking participants aged 15 to 40 years with ARMS were recruited from a specialized early psychosis service in Hong Kong. ARMS status was verified by comprehensive assessment of at‐risk mental state (CAARMS). Comorbid Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition non‐psychotic psychiatric disorders at baseline were ascertained using diagnostic interview and medical record review. Assessments encompassing symptom profiles, psychosocial functioning, subjective QoL and a brief cognitive battery were conducted. Results: Forty‐nine (44.5%) ARMS participants were diagnosed as having comorbid non‐psychotic psychiatric disorders at baseline, primarily depressive and anxiety disorders. Binary multiple logistic regression analysis revealed that female gender, more severe depressive symptoms, higher suicidality and poorer global cognitive functioning were independently associated with comorbid diagnosis status. ARMS participants with psychiatric comorbidity displayed significantly more limited extended social networks and poorer subjective QoL than those without psychiatric comorbidity. Conclusion: Comorbid disorders were frequently observed in Chinese ARMS individuals, and were linked to poorer cognition and higher suicide risk. Our findings underscore a potential critical role of psychiatric comorbidity in determining social functioning and subjective QoL in at‐risk individuals. Further longitudinal research is required to clarify trajectories of comorbid disorder status and its prospective impact on clinical and functional outcomes in ARMS populations.